Effect of copper-enriched layers on localized corrosion of aluminium-copper alloys - Arenas-Vara, María Ángeles; Skeldon, Peter; García-Vergara, Sandra Judith (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Copper-enriched layers were developed onto aluminum-copper alloys using alkaline etching in sodium hydroxide, for both, sputter deposited and bulk conditions. Enriched alloys were evaluated by potentiodynamic polarization in sodium chloride solution in order to determine the effect of the enriched layers on the pitting potential of the alloys. Rutherford backscattering spectroscopy was employed to quantify the enrichments and their locations just beneath the alumina-based oxides remaining from the etching. For the sputter deposited aluminum-copper alloys, the results show some scattering of the pitting potential data, and no correlation between pitting potential and the alloy enriched layer. In the case of bulk Al-2wt.%Cu alloy, with the copper in solid-solution, the pitting potential increased for the enriched specimens, indicating also a different pit morphology, with respect to the non-enriched alloy.